European communication and cultural policies framework - García Leiva, Trinidad (Javnost (Ljubljana), 2011)
This article critically examines the framework of European communication and cultural policies with the intention to enable a better understanding of the role that is currently assigned to both fields within the EU agenda. It is argued that the official European discourse has found in the notion of creativity a way to further domesticate culture in order to instrumentally reduce it, as has already been done with communications, to just another sector that can generate further revenue. In consequence, the creative processes have also begun to be taken into account in the formulation of information society and media policies. This is not a surprise from a historical point of view: the paradigm of creativity has been introduced in policy formation processes through the Lisbon agenda and the innovation society logo as a way of deepening the existing trends.
Keywords: Evropa; Europe; European Union; Evropska unija; politics; politika; sociologija politike